Optimizing the family role to prevent bullying behavior - Trihadi, Dayat (Universitas Muhammadiyah Purwokerto, 2019)
Bullying is a phenomenon resulting negative impacts on the perpetrators and victims. The prevalence of bullying is fairly high in several countries of Asia, America and Europe. The solution offered is an approach to solve bullying behavior problems that are implemented comprehensively by involving stakeholders; it does not only focus on individuals as the bullying perpetrators, but other parties including roles of individuals, families and the school environment which must have balanced proportions so that the children have adequate social functioning for their personality and behavior development which is in accordance with the community’s expectations.